Prospective single blinded randomised controlled trial of two orally administered activated charcoal preparations. Issue 1 (1st January 1999) - Boyd, R; Hanson, J
Abstract : OBJECTIVES: To compare two activated charcoal preparations (Carbomix and Actidose-Aqua) in terms of amount ingested and incidence of vomiting after ingestion. METHODS: Single blinded prospective randomised controlled trial. RESULTS: The mean amount of charcoal ingested was Carbomix 26.5 g, Actidose-Aqua 19.5 g. The mean difference was 7 g (95% confidence interval (CI) 1.5 to 12.4 g). The incidence of vomiting was for the Carbomix 6% and the Actidose-Aqua 8%. The mean difference in vomiting was 2% (95% CI -0.8 to 4.8) CONCLUSIONS: Carbomix administration results in an increased amount of activated charcoal ingested after oral administration. Rates of vomiting after activated charcoal administration were low when compared with previously reported rates.